Antifungal activity of clinical Lactobacillus strains against Candida albicans biofilms: identification of potential probiotic candidates to prevent oral candidiasis - Rossoni, Rodnei Dennis [UNESP]; de Barros, Patrícia Pimentel [UNESP]; de Alvarenga, Janaina Araújo [UNESP]; Ribeiro, Felipe de Camargo [UNESP]; Velloso, Marisol dos Santos [UNESP]; Fuchs, Beth Burgwyn; Mylonakis, Eleftherios; Jorge, Antonio Olavo Cardoso [UNESP]; Junqueira, Juliana Campos [UNESP] (Taylor & Francis, 2018)
This study isolated Lactobacillus strains from caries-free subjects and evaluated the inhibitory effects directly on three strains of C. albicans, two clinical strains and one reference strain. Thirty Lactobacillus strains were isolated and evaluated for antimicrobial activity against in vitro C. albicans biofilms. L. paracasei 28.4, L. rhamnosus 5.2 and L. fermentum 20.4 isolates exhibited the most significant inhibitory activity against C. albicans. Co-incubation between these microorganisms resulted in deterrence of biofilm development and retardation of hyphal formation. The hindrance of biofilm development was characterized by the downregulated expression of C. albicans biofilm-specific genes (ALS3, HWP1, EFG1 and CPH1). L. paracasei 28.4, L. rhamnosus 5.2 and L. fermentum 20.4 demonstrated the ability to exert antifungal activity through the inhibition of C. albicans biofilms.
Keywords: Biofilm; Candida albicans; Lactobacillus; mycology; pathogenesis